Multiple biomarker responses in caged benthic gastropods Bellamya aeruginosa after in situ exposure to Taihu Lake in China - Qian Li; Meng Wang; Lei Duan; Yanling Qiu; Taowu Ma; Ling Chen; Magnus Breitholtz; Åke Bergman; Jianfu Zhao; Markus Hecker; Lingling Wu (Environmental Sciences Europe, 2018)
Abstract Background Freshwater sediments have been recognized as a long-term sink and potential source for environmental pollutants released into the aquatic ecosystems. In this study, the sediment quality of Taihu Lake, which is susceptible to anthropogenic contamination, was assessed by a combination of chemical analytical and biological end points. Specifically, the snail Bellamya aeruginosa was caged in situ at two locations representing different pollution levels for different exposure times (7, 14 and 21 days). At each of these time points, biochemical parameters, i.e., phase I biotransformation enzymes ethoxyresorufin-O-deethylase (EROD), the antioxidant enzymes superoxide dismutase and catalase, reactive oxygen species, protein carbonyl content and lipid peroxidation, were evaluated in the hepatopancreas of snails. In addition, surface sediments were collected for analysis of contaminants of concern, including inorganic pollutants, organochlorine pesticides, polychlorinated biphenyls and polybrominated diphenyl ethers. Results Chemical analyses revealed that sediments from Taihu Lake were contaminated with trace elements and organic pollutants. Concentrations of trace elements (Cu, Ni and As) and organochlorinated pesticides (4,4′-DDE) exceeded their corresponding threshold effect level according to the sediment quality assessment values for freshwater ecosystems in Canada, indicating that adverse biological effects may occur. All biomarkers, except EROD activity, were induced in snails during all exposure times. The integrated biomarker response index (IBR) indicated that during the initial exposure phase (7 days), B. aeruginosa were subjected to significant environmental stress, which diminished during later sampling time points. Conclusions Results showed that IBR correlated well with the levels of environmental contaminants, demonstrating the applicability of this biomonitoring approach to complex environmental exposure scenarios.